Is there an optimal financial structure? : some evidence from Singapore listed companies. - Chng, Jong Ling. (2013)
In this study , we investigated the influence industry class , market forces and size have on the capital structure of firms listed on the Stock Exchange of Singapore Mainboard Through our research , we hope to contribute to the teaching and research of finance as well as to help managers in designing a capital structure that would maximize their firm’s value .